2020
DOI: 10.1039/d0re00067a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable chemo-enzymatic preparation of enantiopure (R)-β-hydroxy-1,2,3-triazoles via lactic acid bacteria-mediated bioreduction of aromatic ketones and a heterogeneous “click” cycloaddition reaction in deep eutectic solvents

Abstract: A chemo-enzymatic strategy for the preparation of enantiopure (R)-β-hydroxy-1,2,3-triazoles using a lactic acid bacterium as a whole-cell biocatalyst and a heterogeneous “click” cycloaddition reaction in deep eutectic solvents is disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Since it was first introduced by Sharpless [19] and Meldal, [20] click chemistry has become a privileged reaction in the chemists′ toolbox [21] and it has shown numerous advantages including easy product recovery, inoffensive by‐product formation, modular reaction with wide scope and many inexpensive, readily available starting materials, catalyst, ligands, and so on [22] . Moreover, 1,2,3‐triazoles have found application to a wide variety of research areas, including organic and pharmaceutical chemistry, bioconjugation, drug discovery, polymer, nano‐ and material sciences [21–23] . CuAAc click reactions have been explored and analyzed in many different green solvents and reaction media, including DESs [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first introduced by Sharpless [19] and Meldal, [20] click chemistry has become a privileged reaction in the chemists′ toolbox [21] and it has shown numerous advantages including easy product recovery, inoffensive by‐product formation, modular reaction with wide scope and many inexpensive, readily available starting materials, catalyst, ligands, and so on [22] . Moreover, 1,2,3‐triazoles have found application to a wide variety of research areas, including organic and pharmaceutical chemistry, bioconjugation, drug discovery, polymer, nano‐ and material sciences [21–23] . CuAAc click reactions have been explored and analyzed in many different green solvents and reaction media, including DESs [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Optically active chiral alcohols play an essential role in medicinal chemistry (Brands et al 2003 ; Chen and de Souza 2019 ; Perrone et al 2008 ; Vitale et al 2020 ). ( R )-1-[3-(Trifluoromethyl)phenyl]ethanol (( R )-MTF-PEL) is a key chiral building block for the preparation of neuroprotective compounds like ( R )-3-(1-(3-(trifluoromethyl)phenyl)ethoxy)azetidine-1-carboxamide (Scheme 1 ) (Snape et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing research in DES chemistry, we reported recently on the preparation of valuable heterocycles by (a) nucleophilic substitution (tetrahydrofuran derivatives) [4], (b) heterocyclodehydration reactions (2-aminoimidazoles, 2-pyrazinones, benzoxazines, thiophenes) [5][6][7][8], (c) carbon-sulfur bond-forming reactions [9], (d) directed ortho-metalation and nucleophilic acyl substitution strategies [10], (e) Pd-catalyzed aminocarbonylation of aryl iodides, Suzuki-Miyaura and Sonogashira cross-coupling reactions [11][12][13], (f) Cu-catalyzed C-N coupling reactions [14], and (g) heterogeneous "click" cycloaddition reactions [15] using DESs as environmentally responsible and non-innocent reaction media. Telescoped, one-pot transformations of phenacyl halides to symmetrical 2,5-disubstituted pyrazines (A), through phenacyl azides as intermediates, were also found to take place smoothly using such neoteric solvents (Scheme 1, path a) [16].…”
Section: Introductionmentioning
confidence: 99%